(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Teaching discussion in the reading class plays a significant role in developing students’ critical thinking, comprehension, and communicative competence. Reading is not only a receptive skill but also an interactive process that encourages learners to interpret, analyze, and respond to texts. This article examines the importance of discussion-based activities in reading classes and analyzes effective strategies for integrating discussion into reading instruction. Special attention is given to the role of the teacher, types of discussion tasks, and the benefits and challenges of using discussion in university-level reading classes.